2014
DOI: 10.1039/c3ce42330a
|View full text |Cite
|
Sign up to set email alerts
|

Achieving single domain relaxor-PT crystals by high temperature poling

Abstract: Single domain relaxor-PT crystals are important from both fundamental and application viewpoints. Compared to domain engineered relaxor-PT crystals, however, single domain crystals are prone to cracking during poling. In this paper, based on the analysis of the cracking phenomenon in [001] poled tetragonal 0.25Pb(In0.5Nb0.5)O3-0.37Pb(Mg 1/3Nb2/3)O3-0.38PbTiO3 (PIN-PMN-PT) crystals, the non-180°ferroelastic domain switching was thought to be the dominant factor for cracking during the poling process. A high tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 42 publications
(54 reference statements)
0
29
0
Order By: Relevance
“…The PMN–0.28PT, PMN–0.32PT and PZN–0.15PT single crystals were poled along their respective polar directions, that is, [111], [011] and [001]. To obtain single-domain states, a high-temperature poling approach was used49. For the PMN–0.28PT and PMN–0.32PT crystals, the samples were poled at 100 °C with a 1 MV m −1 E -field, and then cooled to room temperature with the E -field kept on.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PMN–0.28PT, PMN–0.32PT and PZN–0.15PT single crystals were poled along their respective polar directions, that is, [111], [011] and [001]. To obtain single-domain states, a high-temperature poling approach was used49. For the PMN–0.28PT and PMN–0.32PT crystals, the samples were poled at 100 °C with a 1 MV m −1 E -field, and then cooled to room temperature with the E -field kept on.…”
Section: Methodsmentioning
confidence: 99%
“…For all the three crystals, the X-ray diffraction peaks do not show any anomaly over the temperature range of 50–300 K, indicating the lack of any long-range ferroelectric phase transition at cryogenic temperatures. Note: the peak splitting in PZN–0.15PT is due to an incomplete single-domain state, especially around the surface of the sample49. Because of the high lattice parameter ratio c / a (1.023) and the associated mechanical clamping, a fully single-domain state is very difficult to obtain.…”
Section: Figurementioning
confidence: 99%
“…[141]. Although large shear properties have been observed in crystals with single domain state, the single domain crystal is subject to cracking from the large electric field induced strain/stress during the poling process [330]. Fig.…”
Section: The Development Of Relaxor-pt Single Crystalsmentioning
confidence: 99%
“…Fig. 10 shows the strain versus electric field curves for rhombohedral PMN-PT crystals along [001] and [111] directions [42], where very high negative strain was observed in [111] poled crystals (this value is about −0.7 % for [001] poled tetragonal crystals [330]). This is due to the fact that the non-180° ferroelastic domains are not equivalent to [111] direction, as shown in Fig.…”
Section: The Development Of Relaxor-pt Single Crystalsmentioning
confidence: 99%
“…So far, many researchers always focused on relaxor-based ferroelectric single crystal growth using a flux method [6][7][8][9]. In 1997, Park and Shrout also reported that ferroelectric solid solutions PMN-xPT (x=0.33) and PZN-xPT (x=0.09) single crystal exhibited ultrahigh piezoelectric response d 33 and electromechanical coupling factors k 33 , which achieved 1500-1570 pC/N and 90%-92% near the MPB regions, respectively [10][11][12].…”
Section: Introductionmentioning
confidence: 99%